Optimization Model for Relief Distribution After Flood Disaster - Pujiana, Perli; Suwilo, Saib; Mardiningsih (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Logistics planning is critical and a key component in meeting initial emergency needs in the aftermath of a disaster. The rapid and efficient distribution of logistical aid becomes critically important. In such situations, the construction of temporary depots in strategic locations and the determination of optimal distribution routes play an important role in ensuring that logistics aid can be distributed to the affected areas evenly. In this study, the Multi Depot Vehicle Routing Problem (MDVRP) is used which aims to minimize the total cost of distributing logistics aid which includes shipping costs, vehicle usage costs, temporary depot construction costs, and vehicle travel costs from distribution centers to temporary depots, while still meeting constraints such as logistics aid demand, vehicle capacity, area visits, maximum mileage, and depot construction. This model uses two types of vehicles where vehicle  is tasked with carrying logistics aid from the distribution center to the temporary depot and vehicle  is tasked with delivering logistics aid directly to the point of demand.